Effects of Plant Density on Plant Growth before and after Recurrent Selection in Maize. Issue 6 (6th October 2016) - Stein, Michael; Miguez, Fernando; Edwards, Jode
Abstract : Breeding for higher grain yield in maize ( Zea mays L.) using increased selection densities has produced varieties that are adapted to grow at higher population densities. While the effects of density on final grain yield and plant phenotypes are well known, how density affects the early‐season growth of the plant has been less studied. The objective of this experiment was to examine the effects of high planting density on the growth of stalk, tassel, and ear shoots in unselected Iowa Stiff Stalk Synthetic (BSSS) and Iowa Synthetic Corn Borer No. 1 (BSCB1) and in populations that have been selected for high grain yield via a reciprocal recurrent selection program. The selected and unselected populations were planted at four densities ranging from 3.23 to 12.92 plant m −2 in six environments near Ames, IA, over 3 yr. Increased planting density affected plant organ growth timing differently in BSSS and BSCB1. High‐density delayed stalk biomass accumulation in BSCB1 but not BSSS and delayed ear shoot and tassel biomass accumulation in BSSS but not BSCB1. Differences in biomass accumulation and partitioning between unselected populations were generally not observed between selected populations, suggesting that selection caused a convergence in growth patterns between the populations. Increased density lowered maximum growth rates for all plant organs, but reduction in growth rate as a result of density occurred at higher density in selected populations than unselected populations.